Desire: the feelings collection: story about human feelings - Ferreira, Fabio Gonçalves (New horizons, cedic international Islamabad, 2012)
Story about human feelings Love, anxiety, fear, shame, loneliness, joy, desire, sadness, jealousy, anger. How to understand these feelings? In a entertaining way, this book will help your child to learn how to deal with several emotions and feelings. At the end of each story, there are guidelines from a psychologist directed to parents and educators so that children's learning become more effective.